In vitro leaf inoculation studies as an indication of tree foliage susceptibility to Phytophthora ramorum in the UK - Denman, S.; Kirk, S. A.; Brasier, C. M.; Webber, J. F. (PLANT PATHOLOGY, 2005)
Leaves of 11 coniferous and 23 broad-leaved tree species important to UK forestry were tested for their susceptibility to the quarantine pathogen Phytophthora ramorum using a detached leaf assay. Two European and two USA isolates were used. Wounded and unwounded leaves were dipped in zoospore suspensions during summer; conifers were also tested in winter. Successful infection of tissue and amount of necrosis were assessed. Highly susceptible broad-leaved hosts included Aesculus hippocastanum, Fraxinus excelsior, Quercus ilex, Ulmus procera and, to a lesser extent, Castanea sativa, Q. cerris and Q. petraea, together with Umbellularia californica and rhododendrons. Acer pseudoplatanus, Alnus glutinosa, Carpinus betulus, Corylus avellana, Fagus sylvatica, Prunus avium, Q. robur, Q. rubra and Q. suber showed consistently low susceptibility. Conifer species including Abies procera, Picea abies, P. sitchensis, Pseudotsuga menziesii, Sequoia sempervirens and Tsuga heterophylla were also susceptible. Pseudotsuga menziesii and A. procera were severely affected. Pinus contorta, P. nigra var. maritima and P. sylvestris were virtually resistant, while Taxus baccata was only slightly affected. Increased necrosis was apparent on leaves that were wounded prior to inoculation. These results extend the known range of trees that P. ramorum is able to attack and confirm its relative host-nonspecificity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL
Keywords: broad-leaved species; conifers; detached leaf dip assay; foliage; forest species; sudden oak death